An Application of the New Function Method to the Generalized Double sinh-Gordon Equation - Bulut, Hasan; Akturk, Tolga; Gurefe, Yusuf (Amer Inst Physics, 2015)
This paper applies a new approach including the trial equation u' = f(cosh (nu)) based on the hyperbolic function cosh in order to find new traveling wave solutions to the generalized sinh-Gordon equation. By the using of this method, we obtain a new elliptic integral function solution. Also, this solution can be converted into Jacobi elliptic function solution by a simple transformation.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 22-28, 2014 -- Rhodes, GREECE
Keywords: New function method; The generalized sinh-Gordon equation; Elliptic integral function solutions